Research Models for Improving the Quality of Arabic Language Education at Sunan Kalijaga State Islamic University Yogyakarta - Ja’far Sodik, Achmad; Nur Kholis, Muhammad; Sutiah, Sutiah; Samsul Ulum, Mohammad; Rufaiqoh, Elok (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2023)
نماذج البحث في تحسين جودة تعليم اللغة العربية لا تزال ذات أهمية كبيرة لدراستها بشكل أعمق. وذلك إلى أن هذه الدراسة لا تتوقف أبدًا وتستمر دائمًا في أن تكون موضوعًا للنقاش والجدل. وأهداف البحث في هذا البحث هي تحديد الشكل المحدد لنماذج البحث المستخدمة في قسم تعليم اللغة العربية بجامعة سونان كاليجاكا الإسلامية الحكومية يوكياكارتا و وصف الأساليب البحثية المستخدمة في بحوث طلاب قسم تعليم اللغة العربية وفهم آثار النماذج والأساليب البحثية في بحوث طلاب قسم تعليم اللغة العربية على تحسين جودة تعليم اللغة العربية. ويستخدم هذا البحث نهجين، هما النهج الكمي والنهج النوعي. يُستخدم النهج الكمي لوصف أعداد تكرار حدوث الكلمات ومجموعات الكلمات بناءً على البيانات المتاحة. وبينما يُستخدم النهج النوعي لفهم وتمثيل معاني النتائج المستخلصة من البيانات. ومصدر البيانات في هذا البحث يتمثل في شكل وثائق مأخوذة من مكتبة الويب في جامعة سونان كاليجاكا الإسلامية الحكومية يوكياكارتا في عام 2022 والتي بلغ إجماليها .2 عنوانًا لبحوث البكاليريوس في قسم تعليم اللغة العربية. ولجمع البيانات في هذا البحث تم استخدام تقنيات الوثائق. وتقنية التحليل تعتمد على نظرية ستيفان تيتشر، حيث يبدأ جمع البيانات بجمع البيانات، ثم يتم عرضها وتقليلها واستنتاجها. تشير نتائج هذا البحث إلى أن الشكل المحدد لنماذج البحث في قسم تعليم اللغة العربية بجامعة سونان كاليجاكا الإسلامية الحكومية يوكياكارتا ينقسم إلى ثلاثة دراسات في ميدان العلم، وهي ميدان علم اللغة العربية، ومهارات اللغة، وميدان تعليم اللغة. وتُقسم الأساليب البحثية أو الأساليب في بحوث طلاب قسم تعليم اللغة العربية إلى اثنين وهي طرق البحث التجريبية والأساليب الوصفية. وتتنوع النماذج وأساليب البحث المستخدمة من قبل الطلاب بشكل كبير، مما يجعلها مؤشرًا لتحسين جودة تعليم اللغة العربية في هذه الجامعة. Research models in Improving the Quality of Arabic Language Education remains crucial to be explored in-depth. This is because such studies never cease and are constantly debated.The research aims to determine the concrete form of research models in PBA study programme students at UIN Sunan Kalijaga Yogyakarta, to describe the research methods used in the theses of PBA study programme students, and to understand the implications of models and methods of research in the theses of PBA study programme students in improving the quality of Arabic language education. This research uses 2 approaches, namely quantitative approach and qualitative approach. The quantitative approach is used to describe the numbers of the frequency of occurrence of words and word clusters based on existing data. While the qualitative approach is used to understand and represent the meaning of the findings from the data. The data source in this research is in the form of documentation taken from the web library of UIN Sunan Kaijaga Yogyakarta in 2022 which totalled 20 titles of S-1 thesis of PBA study programme. For data collection in this study using documentation techniques. The analysis technique uses Stefan Titscher's theory, namely data begins with collecting data, presented, reduced, and concluded. The results of this study indicate that; the concrete form of the research model of PBA study programme students at UIN Sunan Kalijaga Yogyakarta is divided into three studies in the field of science, namely the field of Arabic language science, language skills and the field of language learning; Research methods or methods in the theses of PBA study programme students are divided into two research methods, namely experimental research methods and descriptive methods; The models and research methods of PBA study programme students at UIN Sunan Kalijaga Yogyakarta vary greatly so that they can be an indicator in improving the quality of Arabic language education at the institution.